Validation of Harmonized Cognitive Assessment Protocol (HCAP) in Egypt: A sub study of the Egyptian Longitudinal study of aging (AL-SEHA) - Ayman Moustafa, Sara (AUC Knowledge Fountain, 2024)
Abstract Building upon the insights gained from the AL-SEHA pilot study, which underscored the pressing need for comprehensive cognitive assessment tools in Egypt, a subsequent research initiative was launched. This initiative sought to address the escalating burden of dementia and Alzheimer's Disease Related Dementias (ADRD) by adapting and validating the Harmonized Cognitive Assessment Protocol (HCAP) for the Egyptian context. The validation study, conducted with 300 participants aged 55 and over, drawn from diverse backgrounds and healthcare settings in Cairo, Mansoura, and Beni Suef, demonstrated the HCAP's effectiveness across different age and education levels within the Egyptian population. The tool exhibited high sensitivity (87.69%) and specificity (88.75%) in detecting cognitive impairment, indicating its potential for reliable early screening. While acknowledging the presence of false positives and negatives, the HCAP's strong performance suggests its value as a tool for identifying individuals who may benefit from further clinical evaluation and potential intervention. This validation study represents a significant step forward in addressing the growing challenge of cognitive decline in Egypt. By providing a culturally adapted and reliable tool for early detection, the HCAP can facilitate timely interventions, potentially delaying the onset of dementia and improving the quality of life for older adults in Egypt